Transformasi Pembelajaran Dengan Teknologi: Analisis Kritis Dari Lensa Teori Post-Positivisme, Kritis, Dan Konstruktivisme - Aulia Ramadhani; Agung Winarno (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Technology has undoubtedly revolutionized the way we learn and acquire knowledge. In recent years, there has been a significant shift towards integrating technology into educational practices, with the aim of enhancing the learning experience for students. This transformation has sparked a debate among educators and researchers about the implications of this shift on the traditional methods of teaching and learning. Some argue that technology has the potential to democratize education and provide equal opportunities for all learners, while others express concerns about the impact of digital distractions and the loss of face-to-face interaction. Through the lens of post-positivism, criticality, and constructivism theory, this critical analysis aims to explore the complexities of the transformation of learning with technology. By examining the underlying assumptions and implications of integrating technology into education, we can gain a deeper understanding of how it may shape the future of learning. This analysis will delve into the various perspectives and theories surrounding the use of technology in education, considering both the benefits and drawbacks. Through a balanced examination of the evidence, we hope to uncover the key factors that will determine the success of technology in shaping the future of learning. Ultimately, the goal is to provide insights that will guide educators and policymakers in making informed decisions about integrating technology into educational practices.